Genetic–environment associations explain genetic differentiation and variation between western and eastern North Pacific rhinoceros auklet (Cerorhinca monocerata) breeding colonies - Brendan A. Graham; J. Mark Hipfner; Kyle W. Wellband; Motohiro Ito; Theresa M. Burg (Ecology and Evolution, 2024)
Abstract Animals are strongly connected to the environments they live in and may become adapted to local environments. Examining genetic–environment associations of key indicator species, like seabirds, provides greater insights into the forces that drive evolution in marine systems. Here we examined a RADseq dataset of 19,213 SNPs for 99 rhinoceros auklets (Cerorhinca monocerata) from five western Pacific and 10 eastern Pacific breeding colonies. We used partial redundancy analyses to identify candidate adaptive loci and to quantify the effects of environmental variation on population genetic structure. We identified 262 candidate adaptive loci, which accounted for 3.0% of the observed genetic variation among western Pacific and eastern Pacific breeding colonies. Genetic variation was more strongly associated with pH and maximum current velocity, than maximum sea surface temperature. Genetic–environment associations explain genetic differences between western and eastern Pacific populations; however, genetic variation within the western and eastern Pacific Ocean populations appears to follow a pattern of isolation‐by‐distance. This study represents a first to quantify the relationship between environmental and genetic variation for this widely distributed marine species and provides greater insights into the evolutionary forces that act on marine species.